School inspections and principals' leadership - Lundgren, Mats (Vodenje v vzgoji in izobraževanju, 2014)
This article is about how criticism from the Swedish Schools Inspectorate affects principals' leadership. The result builds on experiences from an on-going case study that started in the beginning of 2011 and that will be finished in 2015. We present two examples where the local school management and principals try to improve the activities on the basis of the Schools Inspectorate's report. The first example consists of a so called research circle where we as researchers together with a principal and a group of teachers try to develop instruments to meet criticism of shortcomings in an unsafe school environment and poor study environment. The second example describes how the municipality initiated a development project (prio) where schools chart their own needs of development and how they are supposed to take action in order to respond to criticism from the Schools Inspectorate.
Keywords: education; leadership; principals; ravnatelji; schools inspectorate; šolska inšpekcija; Švedska; vodenje